Konsep Urf sebagai Sumber Hukum dalam Islam - Dar Nela Putri (El-Mashlahah, 2020)
ABSTRACTProblems of an increasingly complex society require proper resolution. Islamic law that makes the Al-Qur'an and al-Hadith as the main reference there is a time does not explain Islamic law in detail, while Muslims must live their lives according to Islamic rules, norms and laws are required to always be relevant to the development of increasingly complex times. Ijtihad is needed in dealing with this problem, one of the products of ijtihad is t urf which can be used as a solution and as a source of Islamic law. The method used in this study is a descriptive qualitative analysis research method and includes a type of research that is literature study. Now ‘Urf is something that is known by many people and done by them, both from words or deeds or something left behind. This article discuss the concept of urf which can be used as a source of Islamic law. The results of the discussion of the concept are First, 'Urf must apply continuously or mostly apply. Second, 'Urf which is the legal source for an action must be present at the time the action is held. Third, there is no affirmation (nash) that is contrary to 'URF. Fourth, the use of 'urf will not lead to the exclusion of certain texts from the shari'ah because the texts of shara' must take precedence over 'urf.Keywords: The 'urf Concept, Source of Islamic Law, and Ijtihad Ulama.INTISARIPermasalahan masyarakat yang semakin kompleks menghendaki adanya penyelesaian dengan tepat namun tetap sesuai dengan  hukum Islam berdasarkan Al-Qur’an dan Al-hadist sebagai rujukan utamanya.  Terkadang ada yang tidak dijelaskan oleh keduanya,  ummat Islam harus menjalankan kehidupannya sesuai aturan, norma dan hukum Islam dituntut untuk selalu relevan terhadap perkembangan zaman yang semakin kompleks, maka diperlukan ijtihad para ulama dalam menangani problem ini yang salah satu produk ijtihadnya adalah ‘urf. ‘Urf dapat dijadikan solusi dan sebagai salah satu sumber dalam  hukum Islam. ‘Urf ialah sesuatu yang telah diketahui oleh orang banyak dan mereka mengerjakannya. Artikel ini akan membahas konsep ‘urf  yang dapat dijadikan sebagai sumber hukum Islam tersebut. Adapun hasil pembahasan dari  konsep tersebut adalah Pertama, 'Urf harus berlaku secara kontiniu. Kedua, 'Urf yang dijadikan sumber hukum bagi suatu tindakan harus terdapat pada waktu diadakannya tindakan tersebut. Ketiga, Tidak terdapat  penegasan (nash) yang berlawanan dengan 'urf. Keempat, 'urf digunakan dengan tidak mengesampingkan nash yang pasti dari syari`at.  Sebab nash-nash syara` harus diutamakan atas 'urf.Kata Kunci: Konsep 'urf, Sumber Hukum Islam, dan Ijtihad Ulama.